Price Movements of IPO Stocks during the Lock-Up Period - Kecskés, András (Public Finance Quarterly, 2023)
The main question of the study is whether there is a relationship between the success of stock market launches, i.e. initial public offerings (IPOs), in innovative industries and the stock price movements in the first six months after the IPO. The starting point is the examination of the efficient market theory and the analysis of the types of secondary market price stabilisation processes. Seventy IPOs with shares that had been launched and traded on NASDAQ for at least six months before August 2017 constitute the data examined. The period examined is only six months, as this was the so-called lock-up period. The study focused on the fact that not every IPO in the sample was successful, as indicated by returns and stock prices. The first hypothesis of the author is that the IPO price has a substantial influence on later returns. The second hypothesis stipulates that sector characteristics have an effect on the success of the IPO, and that there are significant differences between the sectors examined regarding return and stock price indicators. Descriptive statistics have clearly shown that for a significant part of the companies the stock market launch was not successful, as shares generated a negative return for investors and owners, and according to the stock prices, the assets of owners decreased by 60 percent from their initial investment. At the first hypothesis, a partial correlation was established, but the IPO price has no effect on later returns mostly. It has been confirmed, however, that performances move in the same direction, which means return levels are correlated, and if a company’s performance is good in the first thirty days, it is likely to be successful in the future as well in terms of returns. The second hypothesis has been partly confirmed, differences among sectors, stock prices and returns have only been found in a few cases. It is important to note, however, that the first six months on the stock exchange do not provide adequate predictions about the future of the company, as we have seen with the shares of Facebook.